1990
DOI: 10.1002/j.1460-2075.1990.tb07423.x
|View full text |Cite
|
Sign up to set email alerts
|

Regional distribution of brain-derived neurotrophic factor mRNA in the adult mouse brain.

Abstract: Brain‐derived neurotrophic factor (BDNF) is a protein that allows the survival of specific neuronal populations. This study reports on the distribution of the BDNF mRNA in the adult mouse brain, where the BDNF gene is strongly expressed, using quantitative Northern blot analysis and in situ hybridization. All brain regions examined were found to contain substantial amounts of BDNF mRNA, the highest levels being found in the hippocampus followed by the cerebral cortex. In the hippocampus, which is also the site… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

37
509
5
3

Year Published

1995
1995
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 939 publications
(554 citation statements)
references
References 36 publications
37
509
5
3
Order By: Relevance
“…Dopaminergic ingrowth is observed only when grafts directly interrupt the cell bodies of nigral neurons, suggesting that levels of BDNF are highest directly surrounding the graft. In situ hybridization studies show BDNF mRNA in the striatum, the target region of nigral neurons (Hofer et al, 1990), but BDNF mRNA is also expressed in the cell bodies of nigral neurons themselves (Friedman et al, 1991;Gall et al, 1992). This finding greatly complicates the classical view of neurotrophic factors but is interesting in light of our results.…”
Section: Bdnf Effects On the Adult Dopaminergic System In Vivomentioning
confidence: 57%
“…Dopaminergic ingrowth is observed only when grafts directly interrupt the cell bodies of nigral neurons, suggesting that levels of BDNF are highest directly surrounding the graft. In situ hybridization studies show BDNF mRNA in the striatum, the target region of nigral neurons (Hofer et al, 1990), but BDNF mRNA is also expressed in the cell bodies of nigral neurons themselves (Friedman et al, 1991;Gall et al, 1992). This finding greatly complicates the classical view of neurotrophic factors but is interesting in light of our results.…”
Section: Bdnf Effects On the Adult Dopaminergic System In Vivomentioning
confidence: 57%
“…49 That we did not detect BDNF mRNA expression in vitro suggests that BDNF in vivo is produced by CNS neurons and glial cells, which is in line with in situ hybridization studies that demonstrated high BDNF mRNA expression, in particular in hippocampal neurons. 89 After PP lesioning, transient upregulation in mRNA expression has been observed in the granular neurons. 90,91 It is, therefore, possible that the unchanged mRNA levels observed in T PLP mice may be the result of a dilution bias because qPCR performed on the entire hippocampus, as in the present study, might underestimate the lesion-induced local changes in cellular mRNA expression.…”
Section: Discussionmentioning
confidence: 99%
“…Increased serotonin or norepinephrine in the synaptic cleft could thus induce a moderate neuronal excitation and, as a consequence, an increase in BDNF synthesis and release. In the regions studied by us, BDNF is synthesized in pyramidal neurons of brain cortex and hippocampus and in the granule neurons of the dentate gyrus, all of which are excitatory, while TrkB is synthesized both in pyramidal and nonpyramidal cells (Cellerino et al, 1996;Hofer et al, 1990;Rocamora et al, 1996). This increased BDNF in the synaptic cleft would bind to and activate TrkB, a proportion of which is in PSDs.…”
Section: Decrease Of Trkb In Psdsmentioning
confidence: 95%
“…BDNF acts on virtually all central neurons, but is synthesized primarily in pyramidal neurons of brain cortex and hippocampus and in dentate granule cells (Hofer et al, 1990;Rocamora et al, 1996), all of which are excitatory. Therefore, we decided to study whether chronic administration of low doses of the antidepressants Flx and Rbx could affect excitatory synapses of brain cortex and hippocampus.…”
Section: Introductionmentioning
confidence: 99%